¡Viejo del alma...! - Urdaneta Gómez, Roberto, 1955- (Bogotá, Colombia : Editorial La Oveja Negra Ltda., 2015)
A compilation of articles written by the author in 1998 about the relationship between him and his father. A relationship, although sometimes seem traumatic, it had unfogettable moments.
Online resource; title from PDF title page (Digitalia, viewed June 3, 2016)
Keywords: Urdaneta Gómez, Roberto, -- 1955- -- Family; Fathers and sons -- Colombia; Electronic books